Fabrication of N/O self-doped hierarchical porous carbons derived from modified coal tar pitch for high-performance supercapacitors. (15th February 2022) - Yin, Fan; Lu, Kun-Lang; Wei, Xian-Yong; Fan, Zi-Chun; Li, Jia-Hao; Kong, Qian-Qian; Zong, Zhi-Min; Bai, Hong-Cun
Graphical abstract: Highlights: N/O self-doped HPCs were successfully prepared by modifying a coal tar pitch. The HPCs own hierarchical porous architecture and high conductivity. The HPCs show high specific capacitance, good rate performance, and cycle stability. The assembled supercapacitors exhibit high energy density and power density. Abstract: Carbon materials with hierarchical porous architecture and high conductivity are highly desired for supercapacitors (SCs), but there is a daunting challenge to prepare them via an ecofriendly and economic route. Herein, a co-activation/graphitization strategy with the aid of KOH and Ni is proposed to fabricate the N/O self-doped hierarchical porous carbons (HPCs), employing coal tar pitch (CTP) modified by fluid catalytic cracking oil as a low-cost precursor. The as-prepared HPCs with a large specific surface area of 2254 m 2 g −1 and appropriate heteroatom doping exhibit a specific capacitance of 368 F g −1 of specific capacitance at 0.5 A g −1 and still retain 270 F g −1 at 20 A g −1 (73.3% capacitance retention rate) in 6 M KOH electrolyte. Besides, the symmetrical SC achieves a maximum energy density of 27.45 Wh kg −1 at a power density of 253 W kg −1 in 1 M Na2 SO4 electrolyte. This work designs a novel route for preparing electrode materials with excellent electrochemical performance and provides a feasible way for the value-added utilization of low-cost CTP.